Atitudes linguísticas de paraibanos em relação ao seu próprio falar - Morais e Lima, Priscila Evangelista (2019)
Portuguese from Paraíba has been the target of sociolinguistic research since the 1990s. However, there is still little work involving attitudes about the different Brazilian speakers, especially about the dialect of Paraiba. The present investigation, therefore, aims to analyze the manifestations of linguistic attitudes of paraibanos in relation to their own speaking. This research is based on the Variation Theory (LABOV et al., 2006 [1968], LABOV, 2008 [1972]) and on conceptions about linguistic attitudes (Lambert et al., 1960; Rodrigues, Assmar e Jablonski, 2009). The research is qualiquantitative and has a direct approach. In order to understand the linguistic evaluation of the speakers, we conducted a sociolinguistic interview with twelve questions. The corpus is composed of 40 informants from the four mesoregions of the State of Paraíba. The results indicate that the participants of all mesoregions see the way of speaking of their linguistic community as a marker of identity not only local, but also regional, since it is part of the cultural heritage of its people. Even among those who affirm that they do not have an accent, in the other answers, these informants have listed specificities in the form of speaking, such as prosodic marks ("dragged" speech) and dialectal traits ("oxente"), which easily identify them as belonging to a community of specific speech. However, despite the recognition of the value of language as a mark of the cultural identity of their community, the majority of the interviewees expressed the manifestations of linguistic attitudes with a negative sense. The "dragged" or "loaded" mode of speech was mentioned with an unfavorable connotation on the part of the paraibanos in question. Participants believe that there is linguistic prejudice in relation to local speech, not only by speakers of other varieties, but also by members of their own language community.